Characterizing neurofibrillary tangle maturity of phosphorylated tau fluid biomarkers in Alzheimer's disease. (December 2021) - Moloney, Christina M.; Labuzan, Sydney A; Tranovich, Jessica; Crook, Julia E.; Siddiqui, Habeeba; Graff‐Radford, Neill R.; Lachner, Christian; Dickson, Dennis W; Mielke, Michelle M.; Murray, Melissa E
Abstract: Background: Phosphorylated tau (p‐tau) cerebrospinal fluid and plasma biomarkers have become more accurate in predicting Alzheimer's disease (AD) pathology. Although p‐tau fluid biomarkers have been studied in vivo for nearly 20 years, tau phosphorylation sites have not been systematically studied in the context of neurofibrillary tangle maturity in the postmortem brain. Neurofibrillary tangles have a lifespan that is defined by three maturity levels: pretangles, mature tangles, and ghost tangles. Our goal was to characterize four tau phosphorylation sites (pT181, pT205, pT217, and pT231) in postmortem brain to determine which neurofibrillary tangle maturity level they preferentially recognize. Method: The FLorida Autopsied Multi‐Ethnic (FLAME) cohort was queried for cases at each Braak stage (I‐VI). We excluded α‐synucleinopathies, TDP‐43 proteinopathies, and non‐AD primary tauopathies, and those lacking available tissue. Ethnoracial diversity was prioritized for final case selection. A total of 24 cases were evaluated with each Braak stage containing 2 males and 2 females. For Braak stages IV‐VI, only cases with a neuropathologic diagnosis of typical AD were selected. Posterior hippocampus was stained by immunohistochemistry for four antibodies: AT270 (pT181), pT205, pT217, and AT180 (pT231). Slides were digitized using Leica's Aperio technology to enable quantification of tau burden in the CA1 subsector and subiculum of the hippocampus. Result: All tau phosphorylation sites recognized pretangles and mature tangles, and rarely recognized ghost tangles. Digital pathology measures of pT181, pT205, pT217, and pT231 burden showed subtle increases from Braak I‐III. A greater increase was observed from Braak IV onward, except in pT217 where the burden decreased from Braak IV to Braak V before maxing out in Braak VI. pT205 and pT217 had the largest increase between Braak III and Braak VI compared to pT181 and pT231. Conclusion: pT181, pT205, pT217, and pT231 recognize primarily early neurofibrillary tangle maturity levels. This finding could explain why these p‐tau sites are recognized in fluids before symptom onset. Future studies will compare these p‐tau sites to other commonly used tau antibodies for AD research, including AT8 and PHF‐1, as well as to in vivo measures in autopsied study participants who underwent antemortem biomarker evaluation.